1999
DOI: 10.1002/(sici)1521-4184(19996)332:6<213::aid-ardp213>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Analgesic Activity of 2-Methyl-2-[1-(3-benzoyl-4-substituted-1,4-dihydropyridyl)]acetic Acid Methyl Esters, Acetic Acids, and Acetamides

Abstract: A group of 2‐methyl‐2‐[1‐(3‐benzoyl‐4‐substituted‐1,4‐dihy‐dropyridyl)] acetic acid methyl esters (7), weak acetic acids (8), and acetamides (9) were designed for evaluation as less acidic non‐ulcerogenic non‐steroidal antiinflammatory drugs (NSAIDs). In this respect, the model compound 2‐methyl‐2‐[1‐(3‐benzoyl‐4‐phenyl‐1,4‐dihydropyridyl)]acetic acid (8a), unlike traditional arylacetic acid NSAIDs, was shown to be a weak acid with a pKa of 9.17. In contrast to arylacetic acid NSAIDs, the α‐methylacetic acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These modulations at the C3-and C5-positions alter tissue selectivity. [11][12][13] The new therapeutic utility of 1,4-dihydropyridine derivatives is a breakthrough in current clinical trials, encompassing their antimicrobial, 14,15 anticoagulant, 16 antihypertensive, 17 analgesic, 18,19 anticancer, 20 cytotoxic, 21 antitumor activities. 22,23 For instance, we previously reported the anticoagulant and antimicrobial activities of 1,4-dihydropyridine derivatives 24 and other pharmaceutical activities such as analgesic 25,26 and anti-inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…These modulations at the C3-and C5-positions alter tissue selectivity. [11][12][13] The new therapeutic utility of 1,4-dihydropyridine derivatives is a breakthrough in current clinical trials, encompassing their antimicrobial, 14,15 anticoagulant, 16 antihypertensive, 17 analgesic, 18,19 anticancer, 20 cytotoxic, 21 antitumor activities. 22,23 For instance, we previously reported the anticoagulant and antimicrobial activities of 1,4-dihydropyridine derivatives 24 and other pharmaceutical activities such as analgesic 25,26 and anti-inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…The development of multidrug resistance is a major obstacle in pharmacology, requiring the constant development of new therapeutics. 1,4-Dihydropyridine derivatives display a broad spectrum of pharmacological activities such as antitumor (Boer and Gekeler, 1995), antihypertensive (Wenzel et al, 2000), anticonvulsant (Surendra Kumar et al, 2010), cytotoxic (Miri et al, 2011), and significant of analgesic activities (Agudoawu et al, 1999, Warren and Knaus, 1981, Ulloora et al, 2013). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some recent studies have shown that application of profen prodrugs could additionally reduce the risk of gastrointestinal injury. Among other profen prodrug types esters of arylpropionic acids have been introduced [8][9][10][11][12][13] The active enantiomers of profens can be synthesized with excellent enantiomeric excesses by stereoselective esterification of racemic carboxylic acid using the enzyme, which react only with one enantiomer to give corresponding carboxylic acid esters. Yield of corresponding esters was analyzed by gas chromatography (GC) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%